Analysis of the Impact of Adoption of Digital Marketing, Access to Tourism Information, Environmental Sustainability Practices, and Festival Uniqueness on Attractiveness and Economic Contribution to Destinations in East Nusa Tenggara - Respati, Rella Dwi; Purnamasari, Betty Nila; Sulistiyono, Arief (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2025)
The effect of adoption of digital marketing, access to tourism information, environmental sustainability practices, and festival uniqueness on destination attractiveness and economic contribution in East Nusa Tenggara is analyzed in this study. Based on the use of a quantitative technique with a sample size of 180 respondents, feedback was obtained using a Likert scale and analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS 3). Results affirm that all four independent variables have significant effects on destination attractiveness, where festival uniqueness had the highest level of influence. In addition, destination attractiveness positively mediates the relationship between these variables and the economic impact, highlighting its role in enhancing the region's tourism industry. This study provides valuable insights for East Nusa Tenggara tourism stakeholders, providing practical recommendations to enhance destination attractiveness and maximize economic benefits through convergent digital marketing, environmental sustainability, festival uniqueness, and destination attractiveness.